2019
DOI: 10.1016/j.adt.2018.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Radiative rates for E1, E2, M1, and M2 transitions in Ne-like Hf LXIII, Ta LXIV and Re LXVI

Abstract: Calculations for energy levels, radiative rates and lifetimes have been performed for three Ne-like ions, namely Hf LXIII, Ta LXIV and Re LXVI, for which the general-purpose relativistic atomic structure package (GRASP) has been adopted. Results are presented among the lowest 121 levels of these ions, which belong to the 2s 2 2p 6 , 2s 2 2p 5 3ℓ, 2s2p 6 3ℓ, 2s 2 2p 5 4ℓ, 2s2p 6 4ℓ, and 2s 2 2p 5 5ℓ configurations, but CI (configuration interaction) has been considered among a much larger number of levels. No m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 22 publications
2
3
0
1
Order By: Relevance
“…In addition, for a few levels, such as 79-84, there are some (minor) differences in energy orderings, but overall there are no (major) discrepancies between calculations with two different codes. This result was expected and has been noted earlier for several ions, including some Ne-like [14,15], although some authors, such as [21], have shown differences of up to ∼2 Ryd, but their calculations are incorrect as discussed in [14,15] and further explained in [22,23] -see also [24] for many other examples of discrepancies. Although a good agreement between the two calculations in our work confirms the accuracy of the calculated energies, we discuss these further below.…”
Section: Sc XIIsupporting
confidence: 80%
See 4 more Smart Citations
“…In addition, for a few levels, such as 79-84, there are some (minor) differences in energy orderings, but overall there are no (major) discrepancies between calculations with two different codes. This result was expected and has been noted earlier for several ions, including some Ne-like [14,15], although some authors, such as [21], have shown differences of up to ∼2 Ryd, but their calculations are incorrect as discussed in [14,15] and further explained in [22,23] -see also [24] for many other examples of discrepancies. Although a good agreement between the two calculations in our work confirms the accuracy of the calculated energies, we discuss these further below.…”
Section: Sc XIIsupporting
confidence: 80%
“…Similarly, with FAC, we have performed mainly three sets of calculations, which are: (i) FAC1, which includes 3948 levels of the same configurations as in GRASP, (ii) FAC2, which includes 17 729 levels arising from all possible combinations of 2*8, (2*7) 3*1, 4*1, 5*1, 6*1, 7*1, (2*6) 3*2, 3*1 4*1, 3*1 5*1, 3*1 6*1, and 3*1 7*1, and finally (iii) FAC3, which includes a total of 93,437 levels, the additional ones arising from (2*6) 4*1 5*1, 4*1 6*1, 4*1 7*1, 5*1 6*1, 5*1 7*1, 6*1 7*1, and 2*5 3*3. These calculations are on the same lines as considered for some other Ne-like ions [14,15].…”
Section: Sc XIIsupporting
confidence: 60%
See 3 more Smart Citations